Eksplorasi Motif Batik Tidayu dalam Perancangan Tipografi sebagai Media Komunikasi Budaya bagi Generasi Z - Dwifitri, Rosa Amelia; Yunianto, Ipung Kurniawan (Visualita Jurnal Online Desain Komunikasi Visual, 2026)
Batik is a form of visual cultural heritage that represents identity and philosophical values; however, its utilization in digital contexts remains limited. The application of batik motifs in digital typeface design is also relatively rare, particularly when accompanied by evaluations of visual perception and readability. This study aims to design a typeface based on the Tidayu batik motif as a medium of cultural communication relevant to Generation Z. A descriptive approach was employed using the Design Thinking framework, which includes the stages of empathize, define, ideate, prototype, and test. Data were collected through literature review, visual observation, interviews, and questionnaires involving 60 Generation Z respondents. The results indicate that the designed typeface possesses a strong visual character and good readability in display usage. The average perception score of 4.11 suggests a generally positive visual reception, although readability decreases in longer texts. The typeface shows potential for use in digital visual communication with further development.